2008
DOI: 10.1080/00288230809510471
|View full text |Cite
|
Sign up to set email alerts
|

Management strategies for an invasive weed: A dynamic programming approach for Californian thistle in New Zealand

Abstract: Invasive plants can cause significant problems in natural and agricultural ecosystems. Although research has already been conducted on the economics of a single-control option for some invasive weeds, we extended the analysis by developing a dynamic optimisation model that evaluates the net benefits of a range of possible control options simultaneously in order to identify the optimal strategy (mix of control options). This paper focuses on Californian thistle (Cirsium arvense) in pasture in New Zealand. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…, 2008). This apparent contradiction with our study arises because Chalak‐Haghighi et al. (2008) assumed that grazing would damage the thistle directly, but did not consider grazing effects on competing species.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…, 2008). This apparent contradiction with our study arises because Chalak‐Haghighi et al. (2008) assumed that grazing would damage the thistle directly, but did not consider grazing effects on competing species.…”
Section: Discussioncontrasting
confidence: 81%
“…, 2004). A modelling study of C. arvense control in New Zealand suggested high infestations could best be controlled by a combination of herbicides and intensive grazing (Chalak‐Haghighi et al. , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The expected efficacy multiplier, E(ζ(ut)), for those strategies that include only a single treatment option (strategies 2–8 and 25) are obtained from the literature, as presented in Table . The expected efficacy multipliers of the strategies that are a combination of more than one control option are calculated from the following formula (from Chalak‐Haghighi et al ) E(ζ(ut))=1Πs=1S((1Efs))where E(ζ(ut)) is the expected efficacy multiplier of control strategy, s = {1, …, S } are control options included in the strategy, and Efs is the efficacy multiplier of control option s (i.e., the proportion of weeds removed).…”
Section: Methodsmentioning
confidence: 99%
“…These studies have generally examined only a small number of discrete control strategies, often only one. IWM approaches that emphasize the use of several control measures (Buckley et al ; Pannell et al ; Chalak‐Haghighi et al ) are often suggested to be the preferred way of controlling invasive weeds, relative to chemical‐only strategies (e.g., Pardo et al ). This study tests this hypothesis, which has rarely been done for environmental weeds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation